INNOVATIVE TEACHING STRATEGIES FOR TEACHING READING: RECIPROCAL TEACHING STRATEGY AND FACE STORY STRATEGY - Santi Oktarina, Putu (Yavana Bhasha : Journal of English Language Education, 2018)
The main task in reading is to develop students' reading skills. This means motivating them to read. Real readers do something with what they read. Actually, students think that reading is an important thing to do. Because by reading they can achieve important goals or answer the questions they want. So, they are motivated to read because while reading they empower or enrich their knowledge. As teachers, we believe when we say "reading is a power". But for students to believe that reading is the power is not easy. Then, the teacher should put them in position to experience the power of reading. This means they must perform tasks and activities that show the power of reading. In their involvement in this reading power, the teacher must prepare interesting reading teaching methods so as not to make them feel that this reading lesson is very boring. The aim of this paper is to explain two teaching reading strategies, here the writers explore reciprocal teaching strategy and the face story strategy.Keywords: Innovative Teaching Strategies, Teaching Reading, Reciprocal Teaching Strategy, Face Story Strategy